Pulsed differential calorimetry of Zn-doped LSCO cuprates - Basilia, G. G.; Kharadze, G. A.; Kvavadze, K. A.; Nadareishvili, M. M.; Brewer, D. F.; Ekosipedidis, G.; Thomson, A. L. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
The low temperature heat capacity measurements on LSCO samples containing Zn impurities have been performed by means of pulsed differential calorimetry technique. The interpretation of the Zn- concentration dependence of the residual g-coefficient in the linear temperature part of Cel(T) at T&lt&ltTc is consistent with a model based on the assumption of the d-wave symmetry of the order parameter of these superconducting copper oxides.